Analisis Dampak Lingkungan Pembangunan Lift Kaca di Kelingking Beach terhadap Stabilitas Tebing dan Keberlanjutan Ekowisata - Wilma Silalahi; Agusman (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
The construction of a glass elevator facility in the Kelingking Beach tourist area located in Nusa Penida has sparked various debates, particularly regarding the possible impact on the stability of the cliffs around the area and the sustainability of ecotourism, which has been the main attraction of the area. This study was conducted with the aim of conducting an in-depth analysis of the environmental impacts caused by the construction process. The analysis covers changes in the geomorphological structure of the area, the potential for increased landslides due to physical intervention, and how all these changes could affect the continuity of nature-based tourism, which has supported the local economy and ecosystem. In its implementation, this study uses a qualitative-descriptive approach that relies on the processing and analysis of secondary data, including reports from the mass media, official government documents, and academic studies focusing on karst cliffs and the development of tourism infrastructure in natural areas. Based on the analysis results, it was found that the construction of the glass elevator has the potential to increase the risk of cliff instability, mainly due to foundation excavation activities and pressure changes that affect the limestone structure that makes up the cliff. Furthermore, the elevator procurement project was deemed not fully aligned with the principles of sustainable ecotourism, due to the lack of involvement of the local community in the planning and implementation process, as well as the potential for environmental degradation that could have a negative impact in the long term. Therefore, this study emphasizes the importance of conducting a thorough and comprehensive evaluation of geological safety aspects, environmental conservation efforts, and effective tourism management so that Kelingking Beach can continue to be maintained as a tourist destination that is not only attractive and popular, but also safe and sustainable for future generations.